(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The use of film formation with natural solvents and inorganic materials is a step towards sustainable practices in pieces of material science work. Materials and Methods: In this research, the chlorophyll obtained from celery was used as a green solvent to dissolve tin sulfide (SnS) and zinc oxide (ZnO) compounds. The thin films produced using chemical thermal spraying techniques were of approximately 150 nanometers in thickness. The technique allowed for controlled decomposition of the composite materials directly on the substrates, which resulted in films that were appropriate for optical and morphological investigations. The incorporation of ZnO to the SnS matrix was done systematically to determine its effect on the films’ characteristics. Results: The incorporation of zinc oxide into tin (IV) oxide sulfide films caused a reduction in transmission and reflectivity of the films and consequently affected their light-matter interactions. The ZnO-containing samples showed a reduction in the optical energy gap, signifying that the bandgap of the materials was effectively lowered. These results indicate that their light absorption in the visible range is improved, which is advantageous for solar cells or photodetectors. Based on these observations, it is fair to claim that the films made of ZnO and SnS are compatible with each other because all films demonstrated less strenuous changes in optical behavior. Conclusion: ZnO incorporation into SnS films processed with chlorophyll solvent modulates both optical and structural characteristics. Further optimization of ZnO concentration and deposition parameters could refine performance for targeted applications.